DAMPAK KEBIJAKAN PENGALIHAN URUSAN PEMERINTAHAN KONKUREN BIDANG PENDIDIKAN MENENGAH ATAS DI PROVINSI RIAU TAHUN 2017 - Nugroho, Galur Setiya; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The transfer of concurrent government affairs in the management of secondary education certainly has an impact on the organizational structure of the provincial and district / city education offices, education budgeting, coordination and transfer of assets from the district / city government to the provincial government. Some districts / cities feel they are not willing to give up their assets because they have been built through district / city APBD funds. The transfer of concurrent government affairs in the education sector certainly has an impact in the preparation of development programs at the provincial and district / city levels. The transition period of transfer of authority from the district / city government to the province needs special attention by various parties concerned so that the transfer does not harm services to the community. This study saw that the process of transferring authority in secondary education in Riau Province was based on an analysis of the theoretical framework of the impact of policy related to the transfer of concurrent government affairs. This research was conducted with a qualitative approach and was carried out in Riau Province. As the main locus of this research is the Riau Provincial Education Office, the data in this study were collected through interviews, observation and review of documentary data. The study found that the effect of the transition of concurrent governmental affairs in the field of senior secondary education to the Riau Provincial Government was quite extensive, namely the impact on budget allocation (regional finance), the impact on the transition of employee status and its consequences for indirect expenditure, the impact of asset transition, the impact on education and education services and the impact on the concurrent government affairs of the wider region. The emergence of these impacts correlates with changes in the regional institutional framework which deals with the education sector (Riau Provincial Education Office). The transfer of concurrent governmental affairs in the field of senior secondary education in Riau Province in fact did not run smoothly, it could be seen from various obstacles in the process of transitioning concurrent government affairs. The factors in question are the area-wide factors that affect organizational performance, regulatory factors due to the lack of ready regional policy frameworks and regional organizational structure factors (Riau Provincial Education Agency). As a result, the data verification and validation process is slow and the mechanism for transferring status to financing, employees and assets is also hampered.Keywords: Authority, Education, Local Government, Decentralization